IMPLEMENTASI PERATURAN DAERAH KOTA PALEMBANG NOMOR 12 TAHUN 2013 TENTANG PEMBINAAN ANAK JALANAN, GELANDANGAN DAN PENGEMIS PASAL 9 AYAT 2 PADA DINAS SOSIAL KOTA PALEMBANG (Studi UPTD Panti Sosial Rehabilitasi Pengemis dan Gelandangan Provinsi Sumatera Selatan) - Helda Fitriani; Holipah Holipah; Asmawati Asmawati (STIA SATYA NEGARA PALEMBANG, 2026)
The purpose of this research is to know the Implementation of Regulations Palembang City Region Number 12 of 2013 Concerning the Development of Street Children, Homeless and Beggars Article 9 Paragraph 2 At the Social Service of Sumatra Province South (Study of Service Technical Implementation Unit (UPTD) Social Rehabilitation Institution Beggars and Homeless South Sumatra Province) and Factors The inhibitor. The method used in this study is the research method qualitative by collecting data through observation, interviews, literature study and documentation. Based on the results of research regarding the Implementation of Regional Regulations Palembang City Number 12 of 2013 Concerning the Development of Street Children, Homeless and Beggars Article 9 Paragraph 2 in the UPTD Social Rehabilitation Institution Beggars and Homeless South Sumatra Province has been carried out successfully particularly good for homeless and beggars, who are in rehabilitation programs the orphanage has provided various guidance for the homeless and beggars include psychosocial diagnosis, mental spiritual guidance, guidance physical education, skills, entrepreneurship and education in accordance with Regional Regulation No. 12 2013 Article 9 Paragraph 2. But there are also inhibiting factors of the target residents where some of the homeless and beggars still live there are those who are lazy, have a low mindset and want to live in an instant way, namely by begging on the streets. Keywords: Personnel Administration, Employee Performance